EFFECTIVENESS OF ENGINEERING GROUP COUNSELING SERVICES PLAYING THE ROLE TO IMPROVE COMMUNICATION ETHICS STUDENT - Auladina Lathifa; Neviyarni (Literasi Nusantara, 2021)
Communication ethics is important for human life, if someone has ethics in communication then the message received or delivered will be responded to well or positively. This study aims to determine the effectiveness of group guidance services with role playing techniques to improve communication ethics. the method in this study is one group pretest-posttest design with a sample of 30 students, data collection using a communication ethics and documentation questionnaire. the results of the analysis showed that the average pretest score was 60.3 after service delivery was obtained on average at posttest 72.4, known as group guidance services with effective role playing techniques to improve students' communication ethics.